2014
DOI: 10.1186/1756-6606-7-8
|View full text |Cite
|
Sign up to set email alerts
|

The development of suckling behavior of neonatal mice is regulated by birth

Abstract: BackgroundAlthough the function of the sensory system rapidly develops soon after birth in newborn pups, little is known about the mechanisms triggering this functional development of the sensory system.ResultsHere we show that the birth of pups plays an active role in the functional development of the sensory system. We first optimized the experimental procedure for suckling behavior using neonatal mouse pups. Using this procedure, we found that preterm birth selectively accelerated the development of sucklin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The second one is focused on the effect of intrauterine exposure to mifepristone on pup's development. However, Dr. Kawasaki and his team have shown that the in utero injection of mifepristone does not affect pups' survival rate, suckling behavior, righting reflex, nor body weight [5,6], therefore suggesting that the effects observed in the mifepristone-treated group reflect changes due to a premature birth.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one is focused on the effect of intrauterine exposure to mifepristone on pup's development. However, Dr. Kawasaki and his team have shown that the in utero injection of mifepristone does not affect pups' survival rate, suckling behavior, righting reflex, nor body weight [5,6], therefore suggesting that the effects observed in the mifepristone-treated group reflect changes due to a premature birth.…”
Section: Limitationsmentioning
confidence: 99%
“…The fetus' brain is also prepared for this transition by slowing down its growth right before birth [3] and dampening its sensibility to pain [4]. Moreover, preclinical studies have recently defined birth as a critical period that initiates the development of brain structures such as the formation of sensory maps [5,6]. For these reasons, changing the time and/or way of being born engender deviations from the original developmental program that may lead to shortand/or long-term consequences [7].…”
Section: Introductionmentioning
confidence: 99%
“…Growth during labor and birth might underlie the defects in neuronal and network wiring and affect an essential period of sensory acquisition and social interactions. Birth itself acts as a triggering signal to accelerate cortical sensory maps and major early functions including suction ( 46 , 47 ). It is suggested that the reduction of the inhibitory actions of GABA and the aberrant synchronized activity generated consequently affect this operation, leading to long-term sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…After birth, the environment is drastically change and the newborn pups start to receive external sensory stimuli and need to interact with other littermates and mother to keep warm and obtain milk ( Weber et al, 2013 ; Toda and Kawasaki, 2014 ). The sensory nervous system deficits may affect the mother-pup and pup–pup interactions ( Toda and Kawasaki, 2014 ). During the first week of life, we also found that homozygous mice often stayed outside the nest.…”
Section: Discussionmentioning
confidence: 99%